Molecular dynamics simulation studies suggests unconventional roles of non-secretary laccases from enteropathogenic gut bacteria and Cryptococcus neoformans serotype D. (April 2018) - Sharma, Krishna Kant; Singh, Deepti; Rawat, Surender
Graphical abstract: Highlights: Laccase of pathogenic bacteria are rich in alanine, gylcine, leucine and methionine. Docking results suggests significant implications of laccase from gut microflora in the immune modulation of the host. Laccase positive gut flora is involved in the metabolism of phosphatidylcholine which promotes cardiovascular diseases. Microbial laccase is also involved in the metabolism of both PGE2 . Abstract: Laccase in Cryptococcus neoformans is covalently linked to the carbohydrate moiety of the cell wall, which allows it to get access to the different substrates for catalyzing their oxidation and therefore plays a vital role in the virulence. The laccase gene (3.0 kb) from C. neoformans serotype D was amplified, cloned and sequenced for protein modeling, docking and simulation studies. The three dimensional homology models of laccase protein from C . neoformans and other pathogenic gut bacteria were docked with selected biomolecules like prostaglandins (PG), membrane phospholipids, neurotransmitters (serotonin) using GOLD software. The GOLDscore values of laccase from C. neoformans docked with prostaglandinH2 (59.76), prostaglandinG2 (59.45), prostaglandinE2 (60.99), phosphatidylinositol (54.95), phosphatidylcholine (46.26), phosphatidylserine (55.26), arachidonic acid (53.08) and serotonin (46.22) were similar to the laccase from enteropathogenic bacteria but showed a better binding affinity as compared to that of the non-pathogenic bacteria (e.g. Bacillus safensis, Bacillus pumilus and Bacillus subtilis ). The RMSD of MD simulation study done for 25 ns using laccase protein from C . neoformans complexed with phosphatidylcholine was found to be highly stable, followed by the laccase-PGE2 and laccase-serotonin complexes. Furthermore, the binding free energy results were found to support the docking and MD simulation results. The present study implies that few candidate ligands can be intermediate substrate in the catalysis of microbial laccases, which can further play some crucial role in the cell signaling and pathogenesis of enteropathogenic gut micro flora and C . neoforman s.